Pengaruh Knowledge Management Dan Jobdesk Terhadap Kinerja Guru Dengan Organizational Citizenship Behaviour (OCB) Sebagai Intervening - Olta Mal Sandi Olta Mal Sandi; Vivi Nila Sari Vivi Nila Sari; Selvi Yona Sari Selvi Yona Sari (Yayasan Tri Edukasi Ilmiah, 2025)
This study aims to examine the effect of Knowledge Management and Job Descriptions on Teacher Performance with Organizational Citizenship Behavior (OCB) as an intervening variable at SMAN 1 Batang Kapas, Pesisir Selatan Regency, West Sumatra. The population in this study consists of 44 respondents. The sample also consists of 44 respondents using a saturated sampling technique. The method used is Structural Equation Modeling (SEM) with Partial Least Squares (PLS) 3.0. The results of the data analysis conclude that there is a significant negative effect of Knowledge Management on Organizational Citizenship Behavior. There is a significant positive effect of Job Descriptions on Organizational Citizenship Behavior. There is a significant negative effect of Knowledge Management on Teacher Performance. There is a significant positive effect of Job Descriptions on Teacher Performance. There is a significant positive effect of Organizational Citizenship Behavior on Teacher Performance. There is an insignificant negative effect of Knowledge Management on Teacher Performance through Organizational Citizenship Behavior as an intervening variable. There is a significant positive effect of Job Descriptions on Teacher Performance through Organizational Citizenship Behavior as an intervening variable.